A study on land compactness of urban agglomeration-example from Beijing-Tianjin-Hebei - Wang, Huiying; Wang, Huimin; Xiong, Xuehan (Frontiers in Environmental Science, 2022)
Compactness, intensity, efficiency and greenness are becoming the goals of regional governance in China. This study, based on the compact development theory, takes the urban agglomeration of Jingjinji as the research object, uses the composite index to construct a compactness index system based on production-living-ecological space and adopts entropy method to measure and analyze the degree of compactness. The results show that there is an obvious internal differentiation in Jingjinji, and the overall situation is not compact. Composed of production, living and ecological spaces, the compactness of the territorial space differs significantly. Production space is of the highest degree compactness, followed by living space and the lowest is ecological space. By comparing each index, compactness degrees of economic factors and municipal production facilities are better than those of the production land and transportation. Compactness degrees of Social factors of living space are more developed than those of residential land and public services. The overall compactness degree of the ecological space is the lowest, but the degrees of compactness are relatively balanced and there are small differences. The compactness degree of the green land is slightly lower than that of pollution treatment.